Fishbowl California [videorecording (DVD)] - MacRae, Michael A.; MacRae, Michael A.; Olson, Steve, 1984-; Flannery, Kate, 1964-; Bowden, Katrina, 1988- (Gravitas Ventures, 2018)
An unemployed, homeless man with no purpose in life finds an unlikely mother figure in an ailing alcoholic woman.